Does ESG Disclosure Help Improve Intangible Capital? Evidence From A-Share Listed Companies - Jun, Wu; Shiyong, Zheng; Yi, Tang (Frontiers in Environmental Science, 2022)
With the disclosure of ESG, the investment related to ESG disclosure has increased, and the trend of changes in corporate profits has shown an "inverted S-shaped" curve. The research shows that, in the initial stage of investment in ESG construction, new ESG investments increase short-term expenditures and reduce profits. With the increase in ESG investment and the advancement of time, the positive effect of the increase in ESG scores on enterprises begins to appear and gradually offsets the cost of ESG investment. However, when the ESG score of a company is raised to a certain level, the marginal effect of continuing to increase ESG investment diminishes. In this study, we use changes in ESG scores to characterize the impact of corporate ESG investment and further analyze the impact of the changes in listed companies’ ESG scores on corporate performance. The research shows that the increase in ESG investment reduces the company’s current net profit but increases the net profit in the future.